Editor's Choice – Reconstruction of the femoro-ilio-caval outflow by percutaneous and hybrid interventions in symptomatic deep venous obstruction. (October 2017) - van Vuuren, T.M.A.J.; de Wolf, M.A.F.; Arnoldussen, C.W.K.P.; Kurstjens, R.L.M.; van Laanen, J.H.H.; Jalaie, H.; de Graaf, R.; Wittens, C.H.A.
Abstract : Objective/Background: Deep venous obstruction is relatively prevalent in patients with chronic venous disease. Endovascular treatments and hybrid interventions can be used to relieve venous outflow obstructions. This paper assesses mid-term clinical outcomes and patency rates in a large cohort after percutaneous and hybrid interventions. Methods: This was a prospectively analysed cohort study. Patients with symptomatic deep venous obstruction who presented at a tertiary referral hospital were divided into three groups: patients who underwent percutaneous stenting for non-thrombotic iliac vein compression syndrome (IVCS group); patients with post-thrombotic syndrome (PTS) treated by percutaneous stent placement (P-PTS group); and PTS patients with obstruction involving the veins below the saphenofemoral junction in which a hybrid procedure was performed, combining stenting with open surgical disobliteration (H-PTS group). Patency rates, complications, and clinical outcomes were analysed. Results: A total of 425 lower extremities in 369 patients were treated. At 60 months, primary patency, assisted primary patency, and secondary patency rates were 90%, 100%, and 100% for IVCS, and 64%, 81%, and 89% for the P-PTS group, respectively. The H-PTS group, showed patency rates of 37%, 62%, and 72%, respectively, at 36 months. Venous claudication subsided in 90%, 82%, and 83%, respectively. At the 24 month follow-up, mean Venous Clinical Severity Score decreased for all patients and improvement in Villalta score was seen in post-thrombotic patients. The number of complications was related to the extent of deep venous obstruction in which patients in the H-PTS group showed the highest complication rates (81%) and re-interventions (59%). Conclusion: Percutaneous stent placement to treat non-thrombotic iliac vein lesions, and post-thrombotic ilio-femoral obstructions are safe, effective, and showed patency rates comparable with previous research. Patients with advanced disease needing a hybrid procedure showed a lower patency rate and more complications. However, when successful, the clinical outcome was favourable at mid-term follow-up and the procedure may be offered to selected patients.